ANALISIS KESULITAN SISWA BERBICARA MENGGUNAKAN BAHASA INGGRIS DI SMKS KRISTEN TORSINA SANGGAU - Gidion Sanggau; Indri Astuti; Eny Enawaty (Institut Pendidikan Tapanuli Selatan, 2023)
This research is intended to find out aspects of students' problems in speaking English at Torsina Sanggau Christian Vocational School. This is a descriptive research by means of a survey. The instrument used in this research was a questionnaire containing 27 closed questions. The population in this research were 190 students of Torsina Sanggau Christian Vocational School and the sample in this research were students of English class X Accounting, X TKJ, XI Accounting, XI TKJ, XII Accounting and XII TKJ at the Christian Torsina Sanggau Vocational School in odd semesters. teaching 2022/2023. The number of samples is 90 students. The information that has been collected is analyzed using a Likert ratio to identify problems faced by students in dialogue using English in class. The results of data analysis prove that there are 2 aspects of students' problems in dialogue using English. The first is the language factor, namely: pronunciation, grammar and vocabulary. The second factor is psychological factors, namely: lack of confidence, shyness, anxiety and motivation. One of the problems students have in having dialogue using English is the worry of being laughed at when making mistakes in articulation, the complexity of making a sentence and the use of tenses, the difficulty of using appropriate vocabulary and the worry of being embarrassed in public. It can be concluded that language aspects and psychological aspects contribute to students' problems in having dialogue using English in English at Torsina Sanggau Christian Vocational School.